2013
DOI: 10.1136/medethics-2012-101311
|View full text |Cite
|
Sign up to set email alerts
|

Honorary authorship in biomedical journals: how common is it and why does it exist?

Abstract: Honorary authorship is relatively common in biomedical publications. Researchers should comply with the International Committee of Medical Journal Editors' criteria for authorship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 17 publications
1
52
1
6
Order By: Relevance
“…Nevertheless, the incomplete response rate is an obvious limitation of the current study. Other recent questionnaires with email invitations among biomedical researchers have obtained response rates between 16 and 53% [26][27][28]. Reasons for the relatively low response rate may be the length of the questionnaire, as well as its complexity (i.e.…”
Section: Limitationsmentioning
confidence: 99%
“…Nevertheless, the incomplete response rate is an obvious limitation of the current study. Other recent questionnaires with email invitations among biomedical researchers have obtained response rates between 16 and 53% [26][27][28]. Reasons for the relatively low response rate may be the length of the questionnaire, as well as its complexity (i.e.…”
Section: Limitationsmentioning
confidence: 99%
“…In respected medical journals it is estimated at 21%, and that number may be much higher in less prominent journals and in certain countries [5] . In a self-reported study 33% of corresponding authors admitted to having honorary authors, and that the practice was found to be more common in Europe and Asia [6] . Wager [7] performed an observational study on prolific authors and found an egregious case in which one author was named on a paper every 10 days.…”
mentioning
confidence: 99%
“…• "guest/gift/honorific authors" 10 (individuals given authorship credit who have not contributed in any substantive way to the research but are added to the author list by virtue of their stature in the organization);…”
Section: Promoting Practices That Protect the Integrity Of Authorshipmentioning
confidence: 99%